PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP PENGUASAAN SIKAP ILMIAH SISWA KELAS V DI SDN SLIPI 01 PAGI TAHUN AJARAN 2018/2019 - Rahmi Hubba; Mimin Ninawati (Prosiding Seminar Nasional Berseri, 2020)
This Study aims to determine the influence mastery o f the scientific attitude by using Team Games Tournamet (TGT) Models for 5th grade students of SDN Slipi 01 Pagi Jakarta of the 2018/ 2019. The research method used is descriptive quantitative research method with Posttest Only Control desaign. The sample used is purposive sampling. In the hypothesis test used t- test obtained tcount 2.67 at the significant= 0.05 ttabel 1.7, thus H0 is rejected which states that there is a significan by using Team Games Tournament (TGT) models on Mastery of the Scientific Attitude of Class V Students of SDN Slipi 01 Pagi Jakarta.